TINJAUAN YURIDIS TERHADAP WANPRESTASI DALAM HAL HUTANG PIUTANG - Jon Hendri; Khoiri Khoiri (JCH (Jurnal Cendekia Hukum), 2018)
Kaselan S.Hut has lent money to Abdul Wahid bin Kosmol with the amount of money of Rp. 162,000,000. But abdul wahid bin kosmol wanprestasi until finally to the court but in the trial, the “majelis hakim”  did not consider the willingness shown by abdul Wahid to pay off the debts to kaselan. The problem of the study was how the judges’s  legal considerations in deciding cases Number 1372 K / PDT / 2008 and how about a way to prove the case Number 1372 K / PDT / 2008. Furthermore, the method of this journal was the type of normative research, the source data obtained from three parts of Primary Legal Material, the decision of the Supreme Court and the “Perdata" case No. 1372 K / PDT / 2008, secondary law materials from books and “hukum tersier”. From the results, its can be explained that the “majelis hakim mahkamah agung” in conducting examination of cases Number 1372 K / PDT / 2008 has been through legal procedures as defined by the law. However, in giving legal consideration in deciding the judgment only based on the validity of the agreement made by both parties, regardless of the "eksepsi" filed by the defendant, because the defendant also has good willingness and proven by the payment of the debt in several times. In reviewing the instruments of evidence the “majelis hakim mahkamah agung” only concerns for the evidence presented by the plaintiff, whereas the witness evidence presented by the defendant is not a part of assessment of the “majelis hakim”.